ANALYSIS OF THE FEASIBILITY STUDY OF THE DOMESTIC WASTE BUSINESS IN SIDENRENG RAPPANG DISTRICT DUCK BONE FLOUR (DUCK BONE FLOUR) - Haryono, Iranita (Agricultural Socio-Economics Journal, 2024)
Duck bone waste which is a domestic waste in Sidenreng Rappang Regency has not been utilized and there is no handler which is feared will pollute the environment. So it is necessary to use it by making it economically valuable by making duck bone flour. The purpose of this study was to analyze the feasibility of investing in duck bone waste (Duck Bone Flour). The method used is a saturated sample where all of the population is a sample because the number of samples is limited. Methods of data analysis using financial analysis. The analytical tool used for the financial aspect uses analysis of the Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI), to determine whether a business is feasible or not. The results showed that the Duckbone Flour Business, from a financial point of view, with a project duration of 10 years and a discount rate of 10%, it proved feasible. An analysis of admission criteria found a payback period (PP) of 6 months and 1 week. Net Present Value (NPV) is IDR 1,730,085,150, Profitability Index (PI) is 1.63% and Internal Rate of Return (IRR) is 32%. This research is important to be carried out as a source of information for the community and the government about the economic value of duck bone waste.